Transforming university education: a systematic review of mathematical modeling in learning - Acero Apaza, Ines Miryam; Zamata Choque, Hugo Walter; Cutipa Laqui, Anibal Javier (Institute of Advanced Engineering and Science, 2025)
This article is focused on analyzing the impact of mathematical modeling on the learning of university students. The starting point is the complexity of the learning process in technological careers, since cognitive, emotional, social and pedagogical elements are involved in this process, therefore, a multidisciplinary approach is required to allow a holistic understanding of educational phenomena. For this purpose, a systematic review was applied following the PRISMA guidelines and 30 research studies available in Scopus, PubMed, and Web of Science were selected. These studies highlight the importance of mathematical modeling in improving education. The results highlight a higher frequency of use for models with structural equations, models related to adaptive profiles and virtual mathematical models. It is concluded that mathematical modeling represents a valuable resource in higher education, which enriches the learning experience and prepares students to face academic and professional challenges. It is impact is manifested in the improvement of conceptual understanding, the strengthening of problem-solving skills and the close linkage between theory and practice.